GROWTH AND YIELD OF BEETROOT (Beta vulgaris L) AS INFLUENCED BY GOAT MANURE AND SUGARCANE MOLASSES WITH HALF DOSAGE OF PHOSPHORUS INORGANIC FERTILIZER - Priyadarshani, W.M.Nadeeka; Seran, Thayamini (Journal of Agricultural Sciences (Belgrade), 2020)
The pot experiment was conducted to study the effect of goat manure and sugarcane molasses on growth and yield of beetroot (Beta vulgaris L.) in sandy regosol. The experiment was laid out in a completely randomized design (CRD) with six treatments. The treatments included inorganic fertilizer (T1), 10 t/ha goat manure alone (T2) and also 10 t/ha goat manure and 50% triple super phosphate (TSP) with 1-4 t/ha sugarcane molasses (T3-T6). The results showed that plant growth parameters (leaf length, leaf petiole length, leaf width, leaf number, fresh weight and dry weight of leaves) were significantly varied among the treatments. And also there was significant difference in diameter of beetroot among the treatments. Significant differences (P<0.05) were observed in fresh weight of beetroot and total plant among the treatments. Fresh weight of root yield and total yield of beetroot per plant were increased in 10 t/ha goat manure, 2 t/ha sugarcane molasses and 50% TSP (T4) and 10 t/ha goat manure, 3 t/ha sugarcane molasses and 50% TSP (T5) when compared to the control treatment (T1). The Total yield of beetroot per m2 was 1792.62 g in T4 and 1402.68 g in T1. The root yield of beet root was increased in T4 than T5 treatment. This study can be concluded that 10 t/ha goat manure with 2 t/ha sugarcane molasses and 50% TSP could be applied for obtaining high yield of beetroot in sandy regosol.